2010
DOI: 10.1021/jp910615y
|View full text |Cite
|
Sign up to set email alerts
|

Crossed-Beam Investigation of O(3P) + C2H5 → C2H4 + OH

Abstract: The reaction dynamics of ground-state atomic oxygen [O((3)P)] with an ethyl radical (C(2)H(5)) in the gas phase was investigated using high-resolution laser spectroscopy in a crossed-beam configuration. An exothermic channel of O((3)P) + C(2)H(5) --> C(2)H(4) + OH was identified, and the nascent distributions of OH (X (2)Pi: upsilon'' = 0, 1) showed significant internal excitations with an unusual bimodal feature of low and high rotational N''-components with neither spin-orbit nor Lambda-doublet propensities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Experimental Studies: The lab-made crossed-beam apparatus for investigating gas-phase reaction dynamics has been described in detail elsewhere. [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] It consists of two radical-source chambers, each pumped by a 6-inch (1400 L s À1 ) baffled diffusion pump, and a scattering chamber, pumped by a 10-inch (3000 L s À1 ) baffled diffusion pump. The average base pressure in the scattering chamber was kept below 2.0 10 À6 Torr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental Studies: The lab-made crossed-beam apparatus for investigating gas-phase reaction dynamics has been described in detail elsewhere. [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] It consists of two radical-source chambers, each pumped by a 6-inch (1400 L s À1 ) baffled diffusion pump, and a scattering chamber, pumped by a 10-inch (3000 L s À1 ) baffled diffusion pump. The average base pressure in the scattering chamber was kept below 2.0 10 À6 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…It builds on previous gas-phase crossed-beam studies. [5][6][7][8][9][10][11][12][13][14][15][16][17] Radical-radical reaction dynamics were investigated as part of ongoing efforts to elucidate the mechanistic and dynamic attributes of the reactions of O( 3 P) with a series of prototypal alkyl radicals, such as allyl, propargyl, tert-butyl (t-C 4 H 9 ), and vinyl, and to identify the general principles that determine their reactivity and mechanisms. Some hydrocarbon species showed intrinsic stability due to resonance stabilization or hyperconjugation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of the reaction of OH radicals with alkenes in combustion and atmospheric chemistry, the reaction of OH with ethene has been the focus of over fifteen theoretical and forty-five experimental studies. The early temperature- and pressure-dependent rate studies found that, at high temperatures, the reaction results in direct H-atom abstraction to form H 2 O + vinyl while, at low temperatures, the reaction is dominated by the addition of the OH to the double bond of ethene. Tully , concluded that the radical adduct formed by the addition mechanism primarily redecomposes to OH + ethene rather than branching to the energetically allowed product channels.…”
Section: Introductionmentioning
confidence: 99%
“…The home-made, crossed-beam apparatus designed for study of gas-phase reactive scattering processes been described in detail elsewhere. [4][5][6][7][8][9][10][11][12][13][14][15] Briefly, for generation of O( 3 P), 12% NO 2 (99.5%, MG Industries) seeded in helium (ultrahigh purity He: 99.999%) at a 2 atm stagnation pressure was irradiated by a 355 nm Nd:YAG laser beam (30 mJ pulse À1 ) near the throat of the supersonic expansion. A second (CH 3 ) 2 CH radical reactant was generated by supersonic flash pyrolysis of the iso-propyl bromide precursor, (CH 3 ) 2 CHBr, which contains a weak C-Br bond (bond dissociation energy of 71.5 kcal mol À1 ).…”
Section: Experiments and Ab Initio Calculationsmentioning
confidence: 99%
“…3 Recently, in a series of papers, this lab reported combined crossed-beam and ab initio investigations of the elementary reactions of O( 3 P) with several prototypal hydrocarbon radicals, including allyl (C 3 H 5 ), propargyl (C 3 H 3 ), t-butyl (t-C 4 H 9 ), and ethyl (C 2 H 5 ). [4][5][6][7][8][9][10][11][12][13][14][15] The alkyl radicals were generated using a supersonic flash pyrolysis source, where the labile precursor molecules underwent a rapid thermal decomposition inside a high-temperature tube, thereby producing clean, jetcooled radical beams without recombination and/or secondary dissociation. 16 With the aid of ab initio and statistical calculations, the challenging experiments showed the existence of unusual dynamic characteristics in comparison with the calculated internal energy distributions of OH products, which have not been observed in the gas-phase reactions of O( 3 P) + closed-shell hydrocarbon molecules.…”
Section: Introductionmentioning
confidence: 99%